Consumo de ultraprocessados e sua associação com a disponibilidade dietética de ferro, anemia e excesso de peso em crianças socialmente vulneráveis de uma capital do nordeste do Brasil - Queiroz, Jonatan Christian de Lima Santos (2023)
The high consumption of ultra-processed foods (UPF) has been raising concerns due to their high caloric intake and lack of essential nutrients in their composition, resulting in multiple malnutrition burdens in early childhood. In this context, iron deficiency is among the most prevalent health problems in childhood and is considered one of the most relevant nutritional deficiencies worldwide. The objective of the study was to evaluate the consumption of ultra-processed foods and their contribution to the availability of dietary iron (DiFe), anemia and nutritional status of children under five years of age, living in situations of social vulnerability, in the city of Maceió-Alagoas. This dissertation consists of a literature review and a results article, in which the consumption of UPF is described and its association with DiFe, presence of anemia and overweight is evaluated. This is a cross-sectional, home-based study, through interviews, with collection of socioeconomic data and the Brazilian Food Insecurity Scale (EBIA), anthropometric assessment, investigation of food consumption through a 24-hour food survey and determination of hemoglobin concentration (CHb). The consumption of ultra-processed foods, the estimation of DiFe through an algorithm, the classification of nutritional status by body mass index by age and the presence of anemia, by CHb, were verified. A total of 443 children participated, of whom 68.2% were 24 months of age or older, 53.7% were male, 89.4% lived in poverty and 77.9% experienced some level of food insecurity. Food consumption from UPF showed an average of 489.4 (342.9) Kcal, corresponding to 39.2 (21.0)% of total calories. 0.54 (0.42) mg of absorbable iron was observed, which was inversely associated with the greater caloric contribution of UPF (β: -0.14; 95% CI: -0.25; -0.03). The highest caloric contribution from UPF was directly associated with the presence of excess weight (OR quartile 4 versus quartile 1: 2.13; 95%CI 1.03; 4.39) and anemia (OR quartile 4 versus quartile 1: 2.22; 95%CI: 1.11; 4.42). In conclusion, we emphasize the importance of public policy interventions aimed at nutritional education and investments to combat UPF consumption, guiding and encouraging access to healthy eating, particularly for the most vulnerable population. In this way, the emergence of nutritional disorders is prevented, both due to dietary iron deficiency and excess calories.